Teaching Writing Narrative Text Through RAFT Technique Using Film to the Maritime Academy Students - Meryanti (Jurnal Educatio FKIP UNMA, 2026)
Writing is one of the essential language skills that enables students to express ideas effectively. However, many students experience difficulties in developing narrative writing due to limited ideas, insufficient grammar mastery, and low motivation. Therefore, this study aimed to investigate the effectiveness of the RAFT (Role, Audience, Format, Topic) technique assisted by film in improving students’ narrative writing ability. This study employed a quantitative approach with a quasi-experimental design using a nonequivalent pretest–posttest control group design. The participants were 50 second-semester students of Suaka Bahari Maritime Academy, divided into an experimental class and a control class. Data were collected through pre-test and post-test writing assessments and analyzed using an independent samples t-test based on the formula proposed by McMillan and Schumacher (2001). The findings indicated that students taught through the RAFT technique assisted by film achieved better writing performance than those taught using conventional instruction. The statistical analysis showed that the obtained t-value (2.35) exceeded the critical t-value (1.997) at the 0.05 significance level, indicating a statistically significant difference between the two groups. These findings suggest that integrating the RAFT technique with film is an effective instructional strategy for enhancing students’ narrative writing ability and increasing their engagement in the writing process.